Co-integration and causality between Tapis crude and stock prices in Malaysia/ Nurul Hidayah Khairi - Khairi, Nurul Hidayah (2018)
Oil-exporting and oil-importing economies are not always the same with oil price Even though contrary outcome of oil price additions is much more obvious in oil importing nations, oil exporters are also affected through their transaction with other countries. Meanwhile in the economy, the influence of oil price movement is not always the equivalent cross different sector and industries. Co-integration tests assistance recognize any significant association among variables. Variables with various trends cannot have H long-run association With each Other, suggesting that there is mostly no support for conclusions based on model allocations (Sjö, 2008), In general, presume that the system is integrated of order I (1) the idea being that international stock markets are likely to be co-integrated under the Johansen co-integration test hypothesis (Yusupov and Duan, 2010) meanwhile many of the Same variables affect market performance, resulting in co-integration in the long run. This study used the causal study because it Will focusing on what is the cause and effect from the independent towards the dependent Besides, this study is vital to identify the co-integration relationship between the dependent and independent variables. This study concluded here is a cointegration between independent variable and dependent variable.